Effects of Vanillic Acid on Dynamic Fermentation Parameter, Nitrogen Distribution, Bacterial Community, and Enzymatic Hydrolysis of Stylo Silage - He, Liwen; Li, Sen; Wang, Cheng; Chen, Xiaoyang; Zhang, Qing (Frontiers in Microbiology, 2021)
Vanillic acid (VA) is a phenolic acid derivative commonly found in plants and foods, with a pleasant creamy odour and pharmacologic activities, which is hypothesized to help improve silage fermentation. The silage profile of stylo silage ensiled with addition of VA was evaluated. The results showed that VA addition resulted in the decrease of pH value (5.22 vs 4.33), dry matter loss (5.37% vs 2.51% DM) and ammonia-N proportion (14.57% vs 1.51% CP) of stylo silage as well as the increase of lactic acid concentration (0.51% vs 1.17% DM), true protein proportion (51.18% vs 58.47% CP) and saccharification yield (113.64 vs 126.40 mg/g DM). Meanwhile, bacterial community of stylo silage was altered, where the relative abundance of Enterobacter, Clostridium and Kosakonia decreased, and that of Commensalibacter and Methylobacterium increased. In conclusion, it is suggested that VA could be used as a novel silage additive to improve silage fermentation and nutrient preservation of stylo silage.